Cotton GalT1 Encoding a Putative Glycosyltransferase Is Involved in Regulation of Cell Wall Pectin Biosynthesis during Plant Development - Qin, Li-Xia (Public Library of Science, 2013)
Arabinogalactan proteins (AGPs), are a group of highly glycosylated proteins that are found throughout the plant kingdom. To date, glycosyltransferases that glycosylate AGP backbone have remained largely unknown. In this study, a gene (GhGalT1) encoding a putative β-1,3-galactosyltransferase (GalT) was identified in cotton. GhGalT1, belonging to CAZy GT31 family, is the type II membrane protein that contains an N-terminal transmembrane domain and a C-terminal galactosyltransferase functional domain. A subcellular localization assay demonstrated that GhGalT1 was localized in the Golgi apparatus. RT-PCR analysis revealed that GhGalT1 was expressed at relatively high levels in hypocotyls, roots, fibers and ovules. Overexpression of GhGalT1 in Arabidopsis promoted plant growth and metabolism. The transgenic seedlings had much longer primary roots, higher chlorophyll content, higher photosynthetic efficiency, the increased biomass, and the enhanced tolerance to exogenous D-arabinose and D-galactose. In addition, gas chromatography (GC) analysis of monosaccharide composition of cell wall fractions showed that pectin was changed in the transgenic plants, compared with that of wild type. Three genes (GAUT8, GAUT9 and xgd1) involved in pectin biosynthesis were dramatically up-regulated in the transgenic lines. These data suggested that GhGalT1 may be involved in regulation of pectin biosynthesis required for plant development.